IMF Staff Papers, Volume 55, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2008)
This special issue is devoted to the Global Economy Model (GEM), a dynamic stochastic general equilibrium models widely used by the IMF and central banks worldwide to study issues that cannot be adequately addressed with reduced-form econometric models or an earlier generation of macromodels whose dynamic equations were not based on strong choice-theoretic foundations. Douglas Laxton discusses the GEM philosophy and explains how its modelers find solutions to their systems of nonlinear equations. Paolo Pesenti then lays out the structure of model in detail, explaining how the various equations in GEM are derived from individual and firm-level self-interested maximizing behavior and how individual decisions interact with government policy rules. The remaining six papers are specific applications of the GEM structure to a variety of real problems and policy issues.